The first snipe fly (Diptera: Rhagionidae) from the Middle Jurassic of Inner Mongolia, China - Zhang, Kuiyan Y.; Yang, Ding; Ren, Dong (Zootaxa, 2006)
The description of the oldest Rhagionidae in China, Sinorhagio daohugouensis gen. et sp. nov., is given as new to science. It comes from the Middle Jurassic Daohugou Formation of Inner Mongolia. The relationships of Sinorhagio and other relevant genera of Rhagionidae are discussed.